Hubungan Antara Efikasi Diri dan Konformitas dengan Career Decision-Making pada Siswa SMA - Laili Hidayah; Ridwan Budi Pramono (Scidacplus, 2026)
Career decision making is an important developmental task for high school students, especially 12ᵗʰ-grade students preparing for future education and career pathways. However, many students still experience confusion in choosing suitable majors and career directions. This study aimed to examine the relationship between self-efficacy and conformity with career decision-making among high school students. A quantitative correlational method was employed, with career decision making as the dependent variable, while self-efficacy and conformity served as independent variables. The participants were 177 twelfth-grade students from SMA Negeri 2 Kudus selected through cluster random sampling. Data were collected using career decision-making, self-efficacy, and conformity scales, then analyzed using two-predictor regression and product-moment correlation. The findings revealed a highly significant relationship between self-efficacy, conformity, and career decision making (R = 0.712; p < 0.001), contributing effectively by 50.6%. Self-efficacy showed a positive and highly significant relationship with career decision making (r = 0.711; p < 0.001), whereas conformity was not significantly related to career decision making (r = -0.102; p = 0.178). These findings highlight the importance of enhancing students’ self-efficacy through career guidance services to support career decision-making and strengthen career information and exploration services.